Optimal allocation of wind-solar storage capacity of microgrid considering carbon emission reduction benefits. Issue 3 (July 2021) - Wang, Xiumei; Zhu, Qianying; Wang, Yuqing
Abstract: In the context of vigorously advocating the transformation of electric energy production to green and low emission, it is very important to rationally allocate the wind-solar storage capacity of micro-grid. Based on this, this paper aims at the micro grid with wind-solar storage. Firstly, the output model of wind-solar storage unit is established, combined with the system scheduling strategy. Then, the optimization objective was to minimize the total cost of investment and operation, and the benefits of carbon emission reduction were taken into account. Genetic particle swarm optimization algorithm is used to solve the optimal capacity allocation. Finally, according to the calculation results of the example, the proposed wind-solar storage capacity configuration considering the benefits of carbon emission reduction can effectively reduce the cost and carbon emissions of the microgrid.